Short-Term Outcomes of Phage-Antibiotic Combination Treatment in Adult Patients with Periprosthetic Hip Joint Infection - Fedorov, Eugeny; Samokhin, Alexander; Kozlova, Yulia; Kretien, Svetlana; Sheraliev, Taalai; Morozova, Vera; Tikunova, Nina; Kiselev, Alexey; Pavlov, Vitaliy (Viruses, 2023)
Implant-associated infections are the most costly problem in modern orthopedics due to the continued increase in the occurrence of antibiotic-resistant bacterial strains that requires the development of new effective antimicrobials. A non-randomized, prospective, open-label, with historical control study on the use of combined phage/antibiotic therapy of periprosthetic joint infection (PJI) was carried out. Forty-five adult patients with deep PJI of the hip joint were involved in the study, with a 12-month follow-up after one-stage revision surgery. Patients from a prospective study group (SG, n = 23) were treated with specific phage preparation and etiotropic antibiotics, whereas patients from a retrospective comparator group (CG, n = 22) received antibiotics only. The rate of PJI relapses in the SG was eight times less than that in the CG: one case (4.5%) versus eight cases (36.4%), p = 0.021. The response rate to treatment was 95.5% (95% confidence interval (CI) = 0.7511–0.9976) in the SG and only 63.6% (95% CI = 0.4083–0.8198) in the CG. The odds ratio for PJI relapse in patients of the SG was 0.083 (95% CI = 0.009–0.742), which was almost 12 times lower than that in the CG. The obtained results support the efficacy of the combined phage-antibiotic treatment of PJI.